PENGARUH PARTISIPASI ANGGARAN,PERAN KUASA PENGGUNA ANGGARAN,KEJELASAN SASARAN ANGGARAN DI MODERASI OLEH BUDAYA ORGANISASI TERHADAP KINERJA APARATUR PEMERINTAH DAERAH (Studi Empiris pada Satuan Kerja Perangkat Daerah Kota Pekanbaru) - Khairul Badri; Azwir Nasir; Rahmiati Idrus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This Study aims to identify and analyze the effect of budgetery participation,the role of authority of the budget user,clarity of budget goal.organizational culture as moderating variabel on the regional government performance.primary data were collected using a survey of civil servant (PNS) in 32 work units (SKPD) Pekanbaru city government consisting of 96 people head on education public and employment head section and sub-section .the sampling technique used purposive sampling,analysis of the data in this study using multiplelinear regression analysis by using spss version 20.0 The result of this study show that organizational culture as moderating variabel has no effect relation the role of authority of the budget user and the regional government performance.Keywords:participation,budgetery,moderation,organizational culture and performance